PARTISIPASI MASYARAKAT DALAM PROGRAM KELUARGA BERENCANA MEDIS OPERASI WANITA DI KABUPATEN SUMEDANG - Fajarudin, Fajar (JRPA - Journal of Regional Public Administration, 2024)
The aim of the research carried out by the researchers was to find out how community participation in the Women's Medical and Surgical Family Planning Program was in Sumedang Regency, what factors hindered it, and how to overcome the obstacles. This research uses qualitative methods with descriptive analysis. Informants were determined using purposive sampling techniques. With informants, Head of Family Planning, Family Planning and Functional/PKB Division Staff. Data collection techniques were carried out using literature study, field study (observation, interviews and documentation) and triangulation. After that, data processing uses data reduction, data display, data conclusion drawing/verification. The results of the research concluded that community participation in the family planning program, medical surgery for women in Sumedang Regency has run optimally in accordance with planning related to the dimensions of community participation, but has not been maximized in the dimension of willingness to take responsibility because there are still many people who have not maximized it. in terms of knowledge about the program. Based on the results of this research, it is recommended to hold discussions/workshops with the community about the Medical Surgery Program, provide information about Medical Surgery for Women (MOW) by utilizing social media and provide special education about the benefits of the MOW program to prospective MOW participants face to face so that have more detailed and in-depth knowledge.